Mellem moral- og personforbrydelse - Om reformeringen af den italienske seksualvoldslovgivning - Reinicke, Kenneth (Kvinder, Køn & Forskning, 1997)
Until 1996 the Italian legislation concerning sexual violence condoned abuse within the family. The legislation reveals that, for generations, Italian women were living without basic civil rights. It took more than 60 years before the Italian parliament accepted that rape was a crime "against the person" and not "against the public moral". The new legislation concerning sexual violence was perceived as a victory for Italian women. But does their victory pose an actual threat to the Italian male-dominated culture? Will it be possible for Italian women to enter the "fields of power" at all?